Réponses

2014-02-09T20:08:10+01:00
A = 5x - 45
B = -3y - 6
C = 6x + 30
D = 9x - 54
E = -12a - 6
F = -6x + 10
G = -48x - 8
H = 14a - 21
M = 15x - 21 - 12x = 3x - 21
N = 35 y - 55 + 8y = 43y - 55
O = 2x + 6 - 7 = 2x -1
P = 5 + 12x + 32 = 12x + 37
Q = 14x² + 6x
R = - 20x² - 15x
S = 18b² - 36b
T = -24x² + 9x
C'est suffisamment détaillé ?
oui c'est tout bon, merci
tu a oublier I J K L..
ah non rien :p
xD
2014-02-09T20:29:08+01:00
A= 5 (x - 9)  B= -3 (4 + 2)            C= 6 (x + 5)   D= 9 (x - 6)    E= -3 (4a - 2)
  = 5x - 45      = -12 + 2 = -10        = 6x + 30        = 9x - 54       = -12a + 6

F= 2 (-3x + 5)  G= 6 (x + 5)    H= 7 (2a - 3)  M= 3 (5x - 7) - 12x               
  = -6x + 10       = -48x - 8        = 14a - 21      = 15x - 21 - 12x = 3x - 21
     
N= 5 (7y - 11) + 84                  O= 2 (x + 3) - 7              P= 5 + 4 (3x - 8)
  = 35y - 55 + 84 = 35y - 29        = 2x + 6 - 7 = 2x - 1       = 9 (3x - 8) = 27x + 72

Q= 2x (3 + 7x)                        R= -5x (3 + 4x)          S= 9b (-4 + 2b)    T= -3x (-3 + 8x)
  = 6x + 14x = 20x                    = -15x - 20x²              = -36b + 18b²      = 9x - 24x²